Inspection of Aircraft Wing Panels Using Unmanned Aerial Vehicles - Vasileios Tzitzilonis; Konstantinos Malandrakis; Luca Zanotti Fragonara; Jose Angel Gonzalez Domingo; Nicolas P. Avdelidis; Antonios Tsourdos; Kevin Forster (Sensors, 2019)
In large civil aircraft manufacturing, a time-consuming post-production process is the non-destructive inspection of wing panels. This work aims to address this challenge and improve the defects’ detection by performing automated aerial inspection using a small off-the-shelf multirotor. The UAV is equipped with a wide field-of-view camera and an ultraviolet torch for implementing non-invasive imaging inspection. In particular, the UAV is programmed to perform the complete mission and stream video, in real-time, to the ground control station where the defects’ detection algorithm is executed. The proposed platform was mathematically modelled in MATLAB/SIMULINK in order to assess the behaviour of the system using a path following method during the aircraft wing inspection. In addition, two defect detection algorithms were implemented and tested on a dataset containing images obtained during inspection at Airbus facilities. The results show that for the current dataset the proposed methods can identify all the images containing defects.